China's Monetary Policy Communication : Frameworks, Impact, and Recommendations - McMahon, Michael; Li, Xiang; Schipke, Alfred (Washington, D.C. : International Monetary Fund, 2018)
Financial markets are eager for any signal of monetary policy from the People's Bank of China (PBC). The importance of effective monetary policy communication will only increase as China continues to liberalize its financial system and open its economy. This paper discusses the country's unique institutional setup and empirically analyzes the impact on financial markets of the PBC's main communication channels, including a novel communication channel. The results suggest that there has been significant progress but that PBC communication is still evolving toward the level of other major economies. The paper recommends medium-term policy reforms and reforms that can be adopted quickly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet